Urinary Incontinence in Women Living in Nursing Homes: Prevalence and Risk Factors: Inkontinensia Urin pada Perempuan yang Tinggal di Panti Werdha: Prevalensi dan Faktor Risiko - Chairul Rijal; Surahman Hakim (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To identify the prevalence of urinary incontinence, the distribution of the type of urinary incontinence and related risk factors in women older than 50 years. Method: This is a descriptive study with cross sectional design. Two hundred and seventy eight women older than 50 years old living in nursing home were interviewed using the Questionnaire for Urinary Incontinence Diagnosis (QUID) that has been translated and validated. The prevalence will be presented in the form of percentage; while the relationship between risk factors and the incidence or urinary incontinence will be analyzed using Chi square test or Fisher’s exact test, as appropriate, and multivariate analysis. Result: Of 278 research subjects, we obtained 95 subjects (34.2%) suffering from urinary incontinence. Moreover, the distribution of the type is 67 subjects (70.5%) with mixed urinary incontinence, 17 (17.9%) with stress incontinence and 11 subjects (11.6%) with urge incontinence. Body mass index (BMI) showing overweight and obesity are not related with the prevalence of urinary incontinence (p>0.05), which may be caused by the low number of subjects with overweight and obesity. Meanwhile, factors related to urinary incontinence are age older than 60 years (OR=7.79, p=0.021), menopause 10 years (OR=5.08, p=0.004) and multiparity (OR=1.82, p=0.019). Based on multivariate analysis, the risk factor of age older than 60 years is no longer related to urinary incontinence (p>0.05). Thus it can be inferred that age older than 60 years is not a singular factor causing urinary incontinence but rather a part of a multifactorial model. Conclusion: This study shows that the prevalence of urinary incontinence in women living in nursing home is 34.2%; while the distribution of the urinary incontinence is 67 subjects (70.5%) with mixed urinary incontinence, 17 subjects with stress incontinence (17.9%) and 11 subjects (11.6%) with urge incontinence. Risk factors for urinary incontinence are menopause 10 years and multiparity. Keywords: mixed urinary incontinence, menopause, multiparity, prevalence, stress incontinence, urge incontinence, urinary incontinence, Questionnaire for Urinary Incontinence Diagnosis (QUID)